Characteristics of pathogenic fungi and antifungal therapy in cystic fibrosis - Müller, Frank-Michael; Seidler, Marc (Expert review of anti-infective therapy, 2010)
A defective mucociliary clearance facilitates colonization with bacteria and fungal spores in cystic fibrosis patients. Yeasts and molds are cultured from the cystic fibrosis respiratory tract and often their clinical relevance is unknown. Candida spp. are the most commonly isolated yeasts, whereas Aspergillus spp., Scedosporium apiospermum, as well as Exophiala dermatitidis in some countries, are the most frequent molds recovered from respiratory specimens. Molecular biotyping studies have revealed that some fungal genotypes are capable of chronically colonizing the airways. Persistent Aspergillus fumigatus infection is associated with an increased risk of pulmonary exacerbations requiring hospitalization. The prevalence of non-Aspergillus molds may be underestimated due to overgrowth of Pseudomonas and Aspergillus spp. on routine media. Allergic bronchopulmonary aspergillosis is usually treated by oral steroids and an antifungal azole drug. Interactions with the co-medication have to be considered. A small number of antifungal pharmacokinetic studies indicate a high inter-subject variability for itraconazole, voriconazole and posaconazole, and therefore therapeutic drug monitoring is recommended.
Erstmals am 10 Jan 2014 online veröffentlicht
Gesehen am 10.05.2023